Analisis Penerapan Layanan E-Government pada UPT Keluarga Berencana Kota Tangerang - Bunga Nabila; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Pusat Riset dan Inovasi Nasional, 2024)
E-government is a government effort to provide efficient and effective public services by utilizing information and communication technology. E-Government allows people to access various available services. The aim of this research is to find out how the E-Government service system is implemented, including the factors that influence it, and the benefits of implementing E-Government in public services. This research also uses a purposive sampling technique, namely a technique carried out by determining special criteria or considering certain characteristics of the sample or research subject to be studied that are relevant to the topic. The results of the research show the implementation of UPT KB Tangerang City is not yet optimal, both in terms of the synergy between agencies in the Tangerang City government and the UPT itself in implementing the E-Government system which is still lacking, and the low level of understanding and socialization of employees in implementing it. E-Government service system. To improve e-government management, it is required to integrate information systems for e-government management sequentially to improve public service performance, and increase human resources who are skilled in information technology, the implementation of E-Government at UPT KB can run more optimally and provide greater benefits for the community.